(untitled) (Al-Academy, 2019)
The study (Quality in the Industrial Products Designs and its Reflection on Achieving Competitive Advantage) focused on developing the products in a way that satisfies human desires through the impact of technology on products design systems and performance enhancement. The study question is: how to effectively achieve quality in industrial products designs that influences competitiveness? The aim of the research is to show the design contexts for the product and its reflection on competitiveness. The study is limited to (LG) products in 2017-2018. The results and conclusions reached at by the researcher are included in the study.The sample models adopted contexts, forms and relational relations transcending traditional contexts and forms in the first model by 50%. Let alone what the second model came with of an unfamiliar shape and utilization nature by 50%, because it took a different shape that achieved the principle of quality in use. The most important conclusions are: The products efficiency responds as a result of its response to different types of quality contexts and achieves the objectives related to the nature of their performance. The sense of competence in this aspect is directly connected to the high response of the functional performance inputs for the type of quality contexts, which is connected to satisfaction that the user derives from the product’s ability to achieve the objectives with high quality and efficiency, and as a result of feeling satisfied